Direct selection of cDNAs using whole chromosomes. - Rouquier, S (1995)
We have developed a method for direct selection of cDNAs using whole chromosomes as target DNA. Double-strand cDNAs were synthesized from human fetal brain polyadenylated mRNAs. Flow-sorted chromosomes 17 and 19 were amplified by degenerate oligonucleotide primed polymerase chain reaction (DOP-PCR) and used to capture ds cDNAs by an improved magnetic bead capture protocol. To demonstrate the capabilities of this method, the selected cDNAs were used as probes in FISH experiments. The selected cDNA populations specifically painted chromosomes 17 or 19 on metaphase spreads. These results demonstrate that it is possible to do chromosome painting using cDNA probes and that this method is a means to rapidly select expressed sequences encoded by any portion of the genome.